2007
DOI: 10.1364/oe.15.018111
|View full text |Cite
|
Sign up to set email alerts
|

Point spread function of a collinear holographic storage system

Abstract: A paraxial solution to the coaxial holographic storage algorithm is proposed based on the scalar diffraction theory and a VOHIL model (volume hologram being an integrator of the lights emitted from elementary light sources), which can give insight into the optical characteristics of the collinear holographic storage system in an effective way, including the point spread function and shift selectivity. The paraxial solution shows that the reference pattern is the key issue in the point spread function. Thus, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…( [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], it shows that the PSF is related to the auto-correlation function of the reference pattern times a defocusing phase term. Accordingly, a lens array used as the reference is introduced.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…( [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], it shows that the PSF is related to the auto-correlation function of the reference pattern times a defocusing phase term. Accordingly, a lens array used as the reference is introduced.…”
Section: Discussionmentioning
confidence: 99%
“…The first is to calculate the point spread function (PSF) through Bragg mismatch [10,11]; the second is to apply Fresnel transform to simulate the light field in the recording disc and through Born's approach or the method called "volume hologram being an integrator of the lights emitted from elementary light sources" (VOHIL) to calculate the diffraction pattern on the CCD plane [12][13][14][15]. The procedures of the approaches are described in detaisl from Refs.…”
Section: Basic Theorem 121 Two Models For the Collinear Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies of the holographic storage system, the co-axial lens system has been one of the main issues [9][10][11][12][13]. This lens system is simple and makes it easy to perform the angular multiplexing.…”
Section: Lens Systemmentioning
confidence: 99%
“…In the model, the mirror on the back surface of the holographic disk in the real system is replaced by a double-thickness disk in a modeled transmission algorithm to replace the reflection algorithm in the real system. In previous research, we showed that the PSF for the collinear system can be written 8 as…”
mentioning
confidence: 99%